Respuesta :

Answer:

CORRECT AMONDO

Step-by-step explanation:

Answer:

Rearrange [1] to get an expression for

x

[

3

]

XXXXX

x

=

3

+

3

y

Substitute the expression for

x

from [3] into [2]

[

4

]

XXXXX

2

(

3

+

3

y

)

+

9

y

=

11

Simplify

[

5

]

XXXXX

6

+

6

y

+

9

y

=

11

[

6

]

XXXXX

15

y

=

5

[

7

]

XXXXX

y

=

1

3

Substitute the value of

y

from [7] into [1]

[

8

]

XXXXX

x

3

(

1

3

)

=

3

Simplify

[

9

]

XXXXX

x

=

4

The solution is

(

x

,

y

)

=

(

4

,

1

3

)

Step-by-step explanation: